By Design or by Drift: How, Where, and Why HRM Activities Are Organized in the Public Sector. (March 2018) - Boon, Jan; Verhoest, Koen
In the past decades, scholarship has recognized the potential of human resource management (HRM) to contribute to organizational performance in the public sector. Even so, the issue of how HRM activities are organized to achieve superior performance is still in largely unknown territory. De-centering and re-centering dynamics for the organization of HRM have been recognized, but insufficiently analyzed in terms of theoretical and analytical integration. This study investigates the specifics of how the public sector organizes a variety of HRM activities, including the questions of where and why. We find that a complementary use of a rational design perspective and a constraining drift perspective is crucial in order to fully understand the complexities of organizing HRM activities in the public sector. Public organizations generally intend to seek the most optimal arrangement but are sometimes constrained from doing so. Institutional constraints sometimes result in more optimal arrangements, but they can also lead to unintended side-effects. This calls for more research on how design and drift factors intertwine.